PERBANDINGAN ANALISIS KLASIFIKASI ANTARA DECISION TREE DAN SUPPORT VECTOR MACHINE MULTICLASS UNTUK PENENTUAN JURUSAN PADA SISWA SMA - Rizky Ade Putranto; Triastuti Wuryandari; Sudarno Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Data mining is a process that employs one or more of Machine Learning techniques to analyze and extract knowledge automatically. Analysis of data mining is to determine the classification of a new data record into one of several categories that have been defined previously, also known as Supervised Learning. Classification Decision Tree is one of the well-known technique in data mining and is one of the popular methods in the decision making process of a case in which the method is obtained entropy criteria, information gain and gain ratio. Classification Support Vector Machine Multiclass (SVMM) is known as the most advanced machine learning techniques to handle multi-class case where the output of the data set has more than two classes or categories. This final project aims to compare the level of accuracy and error rate of Decision Tree classification and prediction majors SVMM for high school students at SMAN 1 Jepara. The total accuracy of 88,57% and 11,43% error rate for the classification decision tree and the total accuracy of 87,14% and the error rate for the classification SVMM 12,86%. Keywords : Data Mining, Machine Learning, Supervised Learning, Decision Tree, Support Vector Machine Multiclass